Lymphatic nodular staging and survival in patients operated due to non-small cell lung cancer - Ana María Nazario Dolz; Gilberto Carlos Falcón Vilariño; Dunia Álvarez Matos; Zenén Rodríguez Fernández; Lázaro Ibrahim Romero García (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: In the patients with lung cancer it is vital the surgical treatment, because it facilitates a meticulous pathological staging, as well as a prognosis and treatment according to each patient tumoral charge. Objective: To determine the influence of the mediastinal limphadenectomy type in the survival of patients operated due to non-small cells lung cancer. Methods: A descriptive and longitudinal study was carried out in the General Surgery Service of Saturnino Lora Teaching Clinical-Surgical Provincial Hospital in Santiago de Cuba, during 10 years (from 2009 to 2019), in 55 patients selected at random who received some type of mediastinum lymphadenectomy besides lung resection. In the statistical processing, the absolute number, percentage and the mean were used, as summary measures; also the chi-squared test to identify the possible association among variables, and the Kaplan-Meier method, to specify survival. Results: The most used medistinic lymphadenectomy technique was the ganglionar sampling (47.3 %), with which a higher percentage of negative results was also obtained (84.6) as regards neoplastic invasion, contrary to that is observed with the systematic ganglionar dissection that  revealed metastasis positivity in a high number of the patients that received it (52.9 %). Likewise, patients operated by means of systematic ganglionar dissection showed a better survival 6 months later (100 %) and a year later (87.5 %); after 5 years the survival number with this technique was superior to all the types of ganglionar excisions practiced. Conclusions: There was a higher probability of the mediastinic lymphatic infiltration diagnosis and better survival in the patients treated with systematic ganglionar dissection. Reason why, it is recommended to protocolize this surgical treatment, which could be endorsed by a clinical trial that allows to compare homogeneous groups that receive each type of lymphadenectomy, respectively, in order to obtain an outstanding and conclusive scientific evidence.